长圆形囊式气囊隔振器横纵向刚度特性研究 - 李东方; 赵应龙 (Jixie qiangdu)
As an effective vibration absorber,the lateral stability of the airbag isolator is closely related to the lateral stiffness.In order to understand and grasp theoretically the transverse and longitudinal stiffness characteristics of the long round bellow-type airbag isolator,according to the lateral and longitudinal force characteristics of the airbag isolator,the transverse and longitudinal stiffness of the airbag isolator from the bladder and the bearing flange were discussed.The theoretical calculation formula of the transverse and longitudinal stiffness of the airbag isolator was put forward.At the same time,the prototype of the corresponding air bag isolator was produced,the lateral and longitudinal stiffness characteristics of the long round airbag were tested.The results show that the error between theory and test results does not exceed 3%,which verifies the effectiveness of the method.And it can be determined that the stiffness provided by the capsule accounts for the main part of the lateral and longitudinal stiffness of the airbag.